2018
DOI: 10.1007/s00125-018-4729-5
|View full text |Cite|
|
Sign up to set email alerts
|

Management of hyperglycaemia in type 2 diabetes, 2018. A consensus report by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD)

Abstract: LeaderT here is a demand from regulators that new treatments for the management of hyperglycaemia in people with type 2 diabetes should not increase cardio vascular risk. 1,2 For most new therapies this will include the performance of a dedicated randomised-controlled cardiovascular outcomes trial (CVOT). This can be conducted prior to licensing, like the SUSTAIN-6 trial with semaglutide, 3 or post-licensing, like the LEADER trial with liraglutide. 4 The results of CVOTs with albiglutide, a once-weekly GLP-1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
1,182
2
71

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,148 publications
(1,283 citation statements)
references
References 256 publications
28
1,182
2
71
Order By: Relevance
“…5 Based on the results of the LEADER trial, liraglutide was recommended as a treatment option in the treatment guidelines for patients with type 2 diabetes and established cardiovascular disease. [7][8][9] For example, triple therapy, which can include the combination of metformin and a GLP-1RA with basal insulin (or oral antihyperglycaemic drugs), is recommended if a patient with type 2 diabetes has not achieved his/her HbA1c target after 3 months of dual therapy. [7][8][9] For example, triple therapy, which can include the combination of metformin and a GLP-1RA with basal insulin (or oral antihyperglycaemic drugs), is recommended if a patient with type 2 diabetes has not achieved his/her HbA1c target after 3 months of dual therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 Based on the results of the LEADER trial, liraglutide was recommended as a treatment option in the treatment guidelines for patients with type 2 diabetes and established cardiovascular disease. [7][8][9] For example, triple therapy, which can include the combination of metformin and a GLP-1RA with basal insulin (or oral antihyperglycaemic drugs), is recommended if a patient with type 2 diabetes has not achieved his/her HbA1c target after 3 months of dual therapy. [7][8][9] For example, triple therapy, which can include the combination of metformin and a GLP-1RA with basal insulin (or oral antihyperglycaemic drugs), is recommended if a patient with type 2 diabetes has not achieved his/her HbA1c target after 3 months of dual therapy.…”
mentioning
confidence: 99%
“…6,7 Consensus guidelines support the combination of a basal insulin and a GLP-1RA as a treatment option for individuals with type 2 diabetes. [7][8][9] Combining injectable therapies consisting of basal insulin and a GLP-1RA, usually with metformin (with or without another noninsulin agent), should also be considered if the patient has not achieved the HbA1c target after 3 months of triple therapy using another regimen, 8 or when blood glucose is ≥16.7 mmol/L, HbA1c ≥ 10% (≥86 mmol/mol) or the patient has symptoms of hyperglycaemia. [7][8][9] Combining injectable therapies consisting of basal insulin and a GLP-1RA, usually with metformin (with or without another noninsulin agent), should also be considered if the patient has not achieved the HbA1c target after 3 months of triple therapy using another regimen, 8 or when blood glucose is ≥16.7 mmol/L, HbA1c ≥ 10% (≥86 mmol/mol) or the patient has symptoms of hyperglycaemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the recent consensus report by the American Diabetes Association and the European Association for the Study of Diabetes included a recommendation for providing patient-centred care that takes multimorbidity into account [36]. Such measures will allow researchers to better map and quantify disease trajectories, in relation to health-related and social outcomes, improving clinical trials and observational studies, and eventually allow clinicians to use these measures in practice to provide more individualized healthcare.…”
Section: Clinical Need and Research Implicationsmentioning
confidence: 99%
“…Although the precise mechanisms behind these benefits have not been fully elucidated, it has been suggested that the reduction in hospitalisation for heart failure may be related to the therapy’s favourable renal, haemodynamic and metabolic effects 16 17. Given the therapeutic role in prevention of heart failure events in at-risk populations, this drug class has been incorporated into the most recent consensus statement by the European Association for the Study of Diabetes and the American Diabetes Association as second-line therapy (after metformin) in patients with type 2 diabetes mellitus with cardiovascular disease 18. Ongoing studies are assessing whether these agents may be useful in the treatment of heart failure, including in those who do not have diabetes mellitus (NCT03036124, NCT03619213, NCT03057977, NCT03057951, NCT03521934).…”
Section: Introductionmentioning
confidence: 99%